Hubungan Bauran Pemasaran Jasa Pelayanan Keperawatan dengan Loyalitas Pasien - Nova Rita (Universitas Airlangga, 2015)
ABSTRACTHigh public interest to go abroad for treatment need to be a particular concern for hospitals in the country. The hospital is not only able to create berkelualitas services but also need to create loyalty to the patient. Loyalty will be created if any implementation of nursing services mix well done. This study aims to determine the relationship of nursing mix shipping services with patient loyalty. This type of survey research with cross sectional analytic study with a sample of 68 people. The way to get the sample with stratified proportional is random sampling. The research result was analyzed by using chi square and logistic regression test. The result of research showed that there is a significant relationship between the marketing mix with nursing service ( product, place, price, promotion, people, and process, as well as physical evidence) with the patient loyalty in which score p > 0,05. A conclusion of the research is simplified that there is a relationship between the marketing mix with hospital service for the patient loyalty. The relationship could be seen at people variable and health insurance with patient loyalty. The development division for service and marketing at hospital is necessary to apply the specific cost as to promote the old patient and the qualified service of nursing. The other major focus want to develop the healthy service of nursing treatment, also provide the patients’ satisfaction, thus it make patients’ loyalty on the installation of hospitality of Ambun Pag.Keywords: mixed, marketing, loyalty, patients